Test of the Bacteriological Ability of Mangrove Nyirih (Xylocarpus granatum) as a Water Disinfectant - Heriyani, Farida; Budiarti, Lia Yulia; Ahdadia, Huda (TROPICAL WETLAND JOURNAL, 2023)
Coliform bacteria contamination in wetlands poses a risk of causing waterborne diseases. Disinfectants are bactericidal, effectively reducing bacterial colonization in water. The coastal plant of mangrove nyirih or Xylocarpus granatum (X.granatum) contains various antibacterial compounds, so it can be used as a natural disinfectant. This study aims to analyze the bacteriological ability of mangrove nyirih as a disinfectant in water samples contaminated with Coliform. This laboratory experimental study used a pretest-posttest control group design. The dilution method was used to observe the effects of 25%, 50%, 75%, and 100% ethanol extract of mangrove leaves (L) and bark (B) of X.granatum as well as chlorine control. The parameters observed were the Coliform Most Probable Number (MPN) and Total Plate Count (TPC) in the test water sample. The results of the study, obtained a decrease in the Coliform MPN and TPC numbers of water samples after treatment. LB100% X.granatum extract produces an effect that is not significantly different from chlorine. In conclusion, mangrove nyirih has the ability as a water disinfectant.